Biophysics Role and Biomimetic Culture Systems of ECM Stiffness in Cancer EMT. Issue 6 (20th March 2022) - Tian, Hao; Shi, Hanhan; Yu, Jie; Ge, Shengfang; Ruan, Jing
Abstract: Oncological diseases have become the second leading cause of death from noncommunicable diseases worldwide and a major threat to human health. With the continuous progress in cancer research, the mechanical cues from the tumor microenvironment environment (TME) have been found to play an irreplaceable role in the progression of many cancers. As the main extracellular mechanical signal carrier, extracellular matrix (ECM) stiffness may influence cancer progression through biomechanical transduction to modify downstream gene expression, promote epithelial‐mesenchymal transition (EMT), and regulate the stemness of cancer cells. EMT is an important mechanism that induces cancer cell metastasis and is closely influenced by ECM stiffness, either independently or in conjunction with other molecules. In this review, the unique role of ECM stiffness in EMT in different kinds of cancers is first summarized. By continually examining the significance of ECM stiffness in cancer progression, a biomimetic culture system based on 3D manufacturing and novel material technologies is developed to mimic ECM stiffness. The authors then look back on the novel development of the ECM stiffness biomimetic culture systems and finally provide new insights into ECM stiffness in cancer progression which can broaden the fields' horizons with a view toward developing new cancer diagnosis methods and therapies. Abstract : Extracellular matrix (ECM) stiffening is not only a disease consequence but also a contributing factor to disease development. ECM stiffness can independently initiate epithelial‐mesenchymal transition (EMT) or act as a costimulatory or "catalyst" in the tumor cell EMT process. Meanwhile, novel ECM stiffness biomimetic culture systems provide more suitable choices for the biophysical study of ECM.